2007
DOI: 10.1108/03090590710721727
|View full text |Cite
|
Sign up to set email alerts
|

Organisational learning and HRD: how appropriate are they for small firms?

Abstract: PurposeThe purpose of this paper is to study human resource development (HRD) and organisational learning issues in a small expert organisation.Design/methodology/approachThis is a qualitative single case study conducted in one Finnish SME. It is part of an ongoing study. It is descriptive in nature and the aim is to find out whether the existing HRD and OL practices are relevant and appropriate in the small context.FindingsThe results reveal that small organisations do consider HRD to be an issue, even though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 54 publications
2
46
0
3
Order By: Relevance
“…Also, 20% of all units exported by South Africa are produced by small and medium-sized enterprises. It is impossible to grow the South African national economy on a sustainable basis without simultaneously achieving sustained growth and development in small and mediumsized enterprises [5]. Swanson [6] has reported that realizing sustained growth and development in small and medium-sized enterprises is a critical requirement for achieving sustained growth and development at the national level.…”
Section: Background Of Studymentioning
confidence: 99%
“…Also, 20% of all units exported by South Africa are produced by small and medium-sized enterprises. It is impossible to grow the South African national economy on a sustainable basis without simultaneously achieving sustained growth and development in small and mediumsized enterprises [5]. Swanson [6] has reported that realizing sustained growth and development in small and medium-sized enterprises is a critical requirement for achieving sustained growth and development at the national level.…”
Section: Background Of Studymentioning
confidence: 99%
“…However, HRD in small organization failed to realize the importance for organizational learning. According to Essi Saru (2007) argued HRD and organizational learning issues form the perspective of small firms. In this study, it argued that learning is about developing the organization or its individual, and therefore it is closely connected to the HRD processes.…”
Section: The Human Resource Development (Hrd) Perspectivementioning
confidence: 99%
“…However, for SMEs which often rely on informal learning (e.g. Mazzarol, 2003;Ellinger and Cseh, 2007;Saru, 2007;Marsick, 2009), their learning practices -whether they develop with growth or not -are still under-researched. Among very few previous studies, Rutherford et al (2003), Jones's (2004), and Kotey and Sheridan's (2004) may be the closest references, which compare human resource management (HRM) practices (including training) in SMEs between growth stages.…”
Section: Literature Reviewmentioning
confidence: 99%